(untitled) (Swiss Medical Weekly, 2012)
OBJECTIVE: In an emergency department, discharge communication represents a key step in medical care. The efficiency of this doctor-patient interaction could be hampered by two bounds: The limited time in emergency care and patients’ mind’s limited capacity to encode, store and maintain information. Such limitations are the focus of this study. Specifically, we examine the number of items physicians deem crucial in a discharge communication and the necessary time estimated to present them. METHODS: A vignette of a patient with chest pain was presented to 47 physicians (38 internists, 9 emergency physicians). Physicians were offered a list of 81 items possibly conveyed to patients and asked to select the important ones assuming a discharge interaction of 15 minutes. Additionally, 7 experts estimated the time required to communicate each item. RESULTS: Physicians’ mean clinical experience was 10.1 years. From the list of 81 items, physicians selected, on average, 36 items (Range: 20–57). Experts rated the time necessary to communicate this subset to be 44.5 minutes – almost three times the preset 15 minutes. While emergency physicians, relative to internists, selected an insignificantly lower number of items (31.6 ± 6.2 vs. 37.4 ± 10.2), the time estimated for communicating the information was significantly shorter (36.9 ± 6.3 vs. 46.4 ± 13.5). CONCLUSIONS: Physicians in our study proved to be miscalibrated with regard to the number of items they could realistically discuss in a discharge communication. We conclude that there is an obvious need to train physicians in skills of implementing efficient discharge communication.